VD_FINDINFO Arrêt / 2013 / 615 vom 2. September 2013 - VD Tribunal cantonal (2013)
RELATIONS PERSONNELLES, MESURE PROVISIONNELLE, REJET DE LA DEMANDE, SURVEILLANCEEN GÉNÉRAL | 273 CC, 445 al. 1 CC, 445 al. 3 CC, 445 CC, 450 CC